Clinical and Paraclinical Findings in Children With Congenital Hepatic Fibrosis: A Single Center 10-Year Study - Seyed Mohsen Dehghani; Amir Saeidi; Farzaneh Nejati; Iraj Shahramian; Ali Bazi; Ali Jangjou; Ali Derakhshan; Morteza Salarzaei; Fatemeh Parooie (Baqiyatallah University of Medical Sciences, 2020)
Background: Congenital hepatic fibrosis (CHF) is an autosomal hereditary disorder affecting the porto-biliary system. It is a rare hereditary disorder often presenting in childhood or adolescence with hepatomegaly, splenomegaly, and gastrointestinal bleeding. A timely diagnosis of organomegalies by sonography can prevent esophageal varices. Liver transplantation is now the only cure for CHF. Objectives: The current study aimed to determine clinical and paraclinical findings in patients diagnosed with CHF from 2008 to 2017. Methods: This was a descriptive cross-sectional study of all children Results: Overall, 32 CHF patients were included during the study period. Of these, 12 (37.5%) and 20 (62.5%) were female and male, respectively. The most frequent clinical presentations at diagnosis were hepatomegaly (81%), splenomegaly (68%), gastrointestinal bleeding (43%), abdominal protrusion (40%), ascites (21%), and epistaxis (6%). Severely enlarged livers were observed in 2 patients. Only 5 patients showed a normal-sized spleen, and kidney sonographic findings were normal in 30 patients. Liver enzymes were not severely deviated from the normal range. There was a significant association between spleen size and esophageal varices (P = 0.01). Overall, 8 patients were liver transplanted due to decompensated cirrhosis. One patient developed bone marrow suppression secondary to the Epstein bar virus and ultimately succumbed to post-transplant lymphoproliferative disorder. In the study period, 2 girls and 2 boys died of disease complications. Conclusion: The results of the present study indicated that the most common clinical findings of CHF in pediatric patients are splenomegaly and hepatomegaly presenting as abdominal distention and gastrointestinal bleeding. Laboratory data can be normal in most cases, but ultrasonographic findings (in liver, spleen, and even kidneys) can be helpful. The present study also showed that patients with splenomegaly are at higher risk of esophageal varices.